2010
DOI: 10.1136/bmj.c2332
|View full text |Cite
|
Sign up to set email alerts
|

Primary total hip arthroplasty versus hemiarthroplasty for displaced intracapsular hip fractures in older patients: systematic review

Abstract: Objective To determine whether total hip arthroplasty is associated with lower reoperation rates, mortality, and complications, and better function and quality of life than hemiarthroplasty for displaced fractures of the femoral neck in older patients. Design Systematic review and meta-analysis of randomised trials, quasirandomised trials, and cohort studies. Data sources Medline, Embase, Cochrane register of controlled trials, publishers' databases, and manual search of bibliographies. Study selection Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
202
5
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(239 citation statements)
references
References 59 publications
19
202
5
5
Order By: Relevance
“…This study raises one of the major issues related to the risk of dislocation in femoral neck fractures. A systematic review [11] showed that single-stage THA may lead to lower reoperation rates and better functional outcomes compared with hemiarthroplasty in patients with displaced femoral neck fractures. If the increased risk of dislocation is confirmed as compared with hemiarthroplasty, surgeons might consider THA if the risk of dislocation can be reduced either by modifying the surgical approach or considering alternative cup designs such as constrained liners and the dual-mobility cup.…”
Section: Discussionmentioning
confidence: 99%
“…This study raises one of the major issues related to the risk of dislocation in femoral neck fractures. A systematic review [11] showed that single-stage THA may lead to lower reoperation rates and better functional outcomes compared with hemiarthroplasty in patients with displaced femoral neck fractures. If the increased risk of dislocation is confirmed as compared with hemiarthroplasty, surgeons might consider THA if the risk of dislocation can be reduced either by modifying the surgical approach or considering alternative cup designs such as constrained liners and the dual-mobility cup.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, surgery in the octogenarian must take into account a number of factors, such as lack of synchronism between physiological age and chronological age, quality of life, risk/benefit ratio and increase in health care costs, an element that is gaining more and more importance [7,19,23,25]. The issue has been settled for other surgical pathologies such as hip fractures [10] or cardiac valve replacement [12]. Secondly, more and more people aged over 80, at greater risk of ground-level falls, have upper cervical spine injuries [19].…”
Section: Discussionmentioning
confidence: 99%
“…The Muscles & soft tissues damage as indicated with serum CK is 5.5 more in posterior than minimally invasive anterior total hip arthroplasty approach [1]. The anterior approach had the early hospital discharge, good rehabilitation, & fewer readmission rates [10,11]. Where subjects operated with the posterior approach reported significantly higher stiffness than anterior subjects, but similar pain and function [12].…”
Section: Introductionmentioning
confidence: 99%